Strategic in/visibility: Does agency make sex workers invisible?. (July 2014) - Ham, Julie; Gerard, Alison
This article examines the links between in/visibility, agency and mobility through the narratives of 55 predominantly indoor sex workers interviewed in Melbourne, Australia, where state government regulations permit some forms of sex work under a licensing framework. This article explores the tensions around the requirement for visibility in the regulation of sex work, the utility of 'strategic' invisibility in the lived realities of sex work and the discursive 'invisibilizing' of sex workers' agency in anti-prostitution discourses. For the workers we interviewed, 'strategic invisibility' was an agentic strategy that prevented stigma and protected social, economic and geographical mobility within and outside the sex industry. In Melbourne, workers' careful management of their 'invisibility' as sex workers contrasted with the state's harm minimization framework that insists on sex workers' visibility within healthcare and licensing systems. This article draws on empirical data to suggest that regulation through licensing can both alleviate and contribute to vulnerabilizing contexts of sex work, providing useful lessons to those considering a similar system of regulation.